TINJAUAN YURIDIS PELAKU USAHA DI BIDANG KULINER YANG TIDAK MEMBERIKAN INFORMASI HARGA DITINJAU DARI ASAS PERLINDUNGAN HUKUM - Leonardo Leonardo; Mariske Myeke Tampi (Fakultas Hukum Universitas Tarumanagara, 2021)
Consumer protection is regulated in Law no. 8 of 1999 concerning Consumer Protection. Article 7 paragraphs (2) and (4) contain the obligations of business actors in carrying out business, as an effort to protect consumers, but this has not been achieved optimally, it can be seen in the phenomenon of business actors in the culinary sector that do not include prices in their food and beverage lists. which then causes losses to consumers because the price charged is unreasonable or excessive. Legal protection for consumers who are victims of such practices is still questionable. Seeing the many cases that have sprung up that have been found on social media, in which cases after getting considerable public attention, the local government then takes action against business actors with sanctions in the form of reprimands to closure, creating a situation where legal certainty and clarity is not created. because it is still unclear whether the practice of not including the price of food and drinks and then charging subjectively based on the willingness of the business actor is an act that is prohibited or not